Efeito da aplicação de cinesioterapia e eletroestimulação no trabalho de parto - CANESIN, Kariny Fleury (2010)
Aiming to evaluate the techniques described in the literature to decrease the time of labor birth and the application of techniques of exercise, massage and transcutaneous electrical nerve stimulation on the active phase of labor and intensity of pain in primiparas. The habit of women to keep moving during labor in an upright position (standing, sitting and / or walking) was a practice more common in some cultures. Historically, the postures and the vertical position change and ambulation have been reported to evolve as efficient dilation, relieve pain during contraction and facilitate the descent of the fetus through the birth canal. We conducted a randomized clinical trial, prospective which was attended by 60 women at the beginning of the active phase with 5 cm of cervical dilation, a public hospital in Goiania in the period July 2009 to July 2010. The women were divided into three groups: control (n = 20), exercise (n =20) and electrical stimulation (n = 20), and monitored during the active phase of labor. During this period, data were collected: Template for recording data (age, weight, height and maternal BMI, race, education), visual analog scale pain, and partograph (gestational age, duration of labor, weight and height of the newborn). In the study, comparing the group of exercise with electrical stimulation and control groups there was a significant difference in the time of labor (p = 0.003). However, in relation to pain intensity difference was not statistically significant (p> 0.05). It is concluded according to the literature there is no way to define a specific technique to encourage labor birth and techniques of exercise, electrical stimulation used in the active phase of labor, the motherspromote progression of labor, but not interfere in its intensity pain.